SUSTAINABLE DEVELOPMENT AND NEIGHBOURHOOD IMPACT STUDY: CONNECTIONS AND CHALLENGES - Bittencourt, Armando Augusto Coelho da Silva; Lima, Fabrício Paiva; Coutinho, Erik Cuellar; da Silva, Josyane Brasil; Cascaes Junior, Octavio Dourado; Gutierrez, Lucy Anne Cardoso Lobão; da Silva, Elzelis Muller; Coutinho, Eliane de Castro (Seven Editora, 2025)
The Neighborhood Impact Study (EIV) aims to identify in advance the possible urban impacts, positive and negative, as a result of the implementation of large-scale enterprises or activities in physical areas within the municipality. For this reason, this research aimed to raise scientific evidence on the advances and challenges for the use of EIV in Brazilian municipalities under the bias of Target 11.1 of the SDG. To this end, as a methodological choice, an Integrative Literature Review was developed through a qualitative approach, considered appropriate to discuss how knowledge has been built about the advances and challenges for the use of EIV and disorderly urban growth and its importance for cities, population and the necessary care for the conservation of the environment. At the conclusion of this research, it was evidenced that the EIV is a tool that, if adopted efficiently, will be able to contribute to the creation of sustainable cities, through the balance between economic growth, environmental protection and social equity. It is worth adding that the content of the research allows us to affirm that it is essential to adopt tools that contribute to the sustainability of cities and thus ensure equitable access to resources and opportunities and improve the quality of life of all residents. DOI: https://doi.org/10.56238/sevened2024.037-143